Microbial production of N-acetyl-D-glucosamine (GlcNAc) for versatile applications: biotechnological strategies for green process development - Das, Sancharini; Chowdhury, Chiranjit; Kumar, S. Pavan; Roy, Debasis; Gosavi, Suresh W.; Sen, Ramkrishna (Carbohydrate Research, 2024)
N-acetyl-D-glucosamine (GlcNAc) is a commercially important amino sugar for its wide range of applications in pharmaceutical, food, cosmetics and biofuel industries. In nature, GlcNAc is polymerised into chitin biopolymer, which is one of the major constituents of fungal cell wall and outer shells of crustaceans. Sea food processing industries generate a large volume of chitin as biopolymeric waste. Because of its high abundance, chitinaceous shellfish wastes have been exploited as one of the major precursor substrates of GlcNAc production, both in chemical and enzymatic means. Nevertheless, the current process of GlcNAc extraction from shellfish wastes generates poor turnover and attracts environmental hazards. Moreover, GlcNAc isolated from shellfish could not be prescribed to certain groups of people because of the allergic nature of shell components. Therefore, an alternative route of GlcNAc production is advocated. With the advancement of metabolic construction and synthetic biology, microbial synthesis of GlcNAc is gaining much attention nowadays. Several new and cuttingedge technologies like substrate co-utilization strategy, promoter engineering, and CRISPR interference system were proposed in this fascinating area. The study would put forward the potential application of microbial engineering in the production of important pharmaceuticals. Very recently, autotrophic fermentation of GlcNAc synthesis has been proposed. The metabolic engineering approaches would offer great promise to mitigate the issues of low yield and high production cost, which are major challenges in microbial bio-processes industries. Further process optimization, optimising metabolic flux, and efficient recovery of GlcNAc from culture broth, should be investigated in order to achieve a high product titer. The current study presents a comprehensive review on microbe-based eco-friendly green methods that would pave the way towards the development of future research directions in this field for the designing of a cost-effective fermentation process on an industrial setup.
Keywords: Genetic engineering; GlcNAc applications; Market status; Microbial bioprocess; N-acetyl-D-glucosamine; synthetic biology